Obligacje komunalne w obrocie publicznym - koszty vs korzyści - Kozuń-Cieślak, Grażyna (Municipal bonds public placement - benefits vs costs, 2006)
At the end of 2005 the value of the municipal bond market was almost 3,3 bn zł and it constituted 20% of the total non - government bond debt market in Poland. Unfortunately among 264 issues only three there were introduced into public trading on the CeTO (the regulated off-exchange market). Such a situation is appearing incomprehensible because of benefits going from public market turnover and quite low expenses of public placement on the CeTO market. The paper presents: methods of municipal bonds issuing, benefits going from public market turnover, cost of introducing municipal bonds to CeTO market turnover.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 215-223